Cognitive and olfactory deficits in Machado-Joseph disease: A dopamine transporter study - Braga-Neto, Pedro; Felicio, Andre C.; Hoexter, Marcelo Q.; Pedroso, Jose Luiz; Dutra, Livia Almeida; Alessi, Helena; Minett, Thais; Santos-Galduroz, Ruth F. [UNESP]; da Rocha, Antonio Jose; Garcia, Lucas A. L.; Bertolucci, Paulo Henrique F.; Bressan, Rodrigo A.; et al. (Elsevier B.V., 2012)
Cognitive and olfactory impairments have been demonstrated in patients with Machado-Joseph disease (MJD), and a possible relationship with dopaminergic dysfunction is implicated. However, there is still controversy regarding the pattern of striatal dopaminergic dysfunction in patients with MJD. In this study, we investigated whether these patients had different Dopamine Transporter (DAT) densities as compared to healthy subjects, and correlated these data with cognitive performance and sense of smell. Twenty-two MJD patients and 20 control subjects were enrolled. The neuropsychological assessment comprised the Spatial Span, Symbol Search, Picture Completion, Stroop Color Word Test, Trail Making Test and Phonemic Verbal Fluency test. The 16-item Sniffin' Sticks was used to evaluate odor identification. DAT imaging was performed using the SPECT radioligand [Tc-99m]-TRODAT-1, alongside with Magnetic Resonance imaging. Patients with MJD showed significantly lower DAT density in the caudate (1.34 +/- 0.27 versus 2.02 +/- 0.50, p < 0.001), posterior putamen (0.81 +/- 0.32 versus 1.32 +/- 0.34, p < 0.001) and anterior putamen (1.10 +/- 0.31 versus 1.85 +/- 0.45, p < 0.001) compared with healthy controls. The putamen/caudate ratio was also significantly lower in patients compared with controls (0.73 +/- 0.038 versus 0.85 +/- 0.032, p = 0.027). Even though we had only two patients with parkinsonisrn, we detected striatal dopaminergic deficits in those patients. No significant correlations were detected between DAT density and cognitive performance or Sniffin' Sticks scores. The data suggests that striatal dopamine deficit is not involved in cognitive or sense of smell deficits. This finding raises the possibility of extra-striatal dopamine and other neurotransmitter system involvement or of cerebellum neurodegeneration exerting a direct influence on cognitive and sensorial information processing in MJD. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Spinocerebellar ataxia type 3; Machado-Joseph disease; Cognitive deficits; Dopamine transporter; Cognition; Olfaction